2012
DOI: 10.5194/acpd-12-15541-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Latitudinal distribution of reactive iodine in the Eastern Pacific and its link to open ocean sources

Abstract: Ship-based Multi-Axis Differential Optical Absorption Spectroscopy measurements of iodine monoxide (IO) and atmospheric and seawater Gas Chromatography – Mass Spectrometer observations of methyl iodide (CH<sub>3</sub>I) were made in the Eastern Pacific marine boundary layer during April 2010 as a part of the HaloCarbon Air Sea Transect-Pacific (HaloCAST-P) scientific cruise. The presence of IO in the open ocean environment was confirmed, with a maximum differential slant column density of 5 &ti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(62 citation statements)
references
References 37 publications
8
53
1
Order By: Relevance
“…They also concluded that the measured iodocarbon precursors were not enough to explain the measured IO mixing ratios and suggested that I 2 could be an additional iodine precursor possibly produced from the deposition of O 3 on the ocean. 226 Mahajan et al 229 have recently reported the latitudinal distribution of reactive iodine in the Eastern Pacific MBL confirming the presence of IO in the open ocean MBL. The IO peak (approximately 1 ppt) was measured over the oligotrophic region of the southeastern Pacific.…”
Section: Iodinementioning
confidence: 72%
“…They also concluded that the measured iodocarbon precursors were not enough to explain the measured IO mixing ratios and suggested that I 2 could be an additional iodine precursor possibly produced from the deposition of O 3 on the ocean. 226 Mahajan et al 229 have recently reported the latitudinal distribution of reactive iodine in the Eastern Pacific MBL confirming the presence of IO in the open ocean MBL. The IO peak (approximately 1 ppt) was measured over the oligotrophic region of the southeastern Pacific.…”
Section: Iodinementioning
confidence: 72%
“…Measurements on a cruise in the East Pacific by Mahajan and co-workers 192 showed maximum IO mixing ratios of 1.2 pmol/mol. They observed a positive correlation with sea surface temperature and salinity but a negative correlation with organic matter in the surface ocean, chlorophyll, and atmospheric ozone.…”
Section: Recent Advances In Tropospheric Halogen Chemistrymentioning
confidence: 95%
“…192,193 At all these locations, comparisons of model results with field data suggest that organic iodine precursors are insufficient to explain the observed levels of IO, 154,177,191 pointing at the importance of I 2 and especially HOI as a source for reactive iodine from the reaction of O 3 on the ocean’s surface. 85,174176 At Cape Verde, I 2 was measured recently 66 showing an increase in its mixing ratio at sunset, a leveling off around midnight and rapid decrease at sunrise.…”
Section: Recent Advances In Tropospheric Halogen Chemistrymentioning
confidence: 98%
“…Laboratory and field data exist, linking very short‐lived iodocarbons and phytoplankton activity [ Smythe‐Wright et al ., ; Hill and Manley , ; Arnold et al ., ; Brownell et al ., ; Lai et al ., ]. However, there is increasing evidence that biological sources of iodine precursors are not the most significant [ Garland and Curtis , ; Reeser et al ., ; Martino et al ., ; Sakamoto et al ., ; Mahajan et al ., ]. Furthermore, it has been shown that iodocarbons are not the major contributor to active iodine in the open ocean MBL but rather inorganic molecules such as I 2 [ Jones et al ., ; Mahajan et al ., ].…”
Section: Introductionmentioning
confidence: 99%